2018
DOI: 10.5152/tjar.2017.33239
|View full text |Cite
|
Sign up to set email alerts
|

Donor Hepatectomy Surgery using Ketamine to Compliment Analgesia and Reduce Morbidity - a Retrospective Chart Review Investigation

Abstract: Objective: Inferior and limited analgesic options/techniques during living donor hepatectomy surgery can result in pain and risks of morbidity, opioid-related adverse events (AEs), predisposition to the development of chronic pain and concerns of potential narcotic abuse. Traditional analgesia uses unimodal intravenous opioids that can cause significant side effects. Ketamine provides analgesia and may be opioid sparing, but use in living-donor hepatectomy has not been studied. Methods: Following human investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…There were no reported technical difficulties or complications of regional or neuroaxial techniques in these cohorts. Adjuvant pharmacological therapies investigated were: Dexmedetomidine, a potent alpha‐2 agonist with hypnotic, sedative, and analgesic properties; ketamine, a NMDA receptor antagonist with sedating, analgesic, and hypnotic actions; intravenous lidocaine, a sodium channel blocker with analgesic properties; ketorolac, a non‐steroidal anti‐inflammatory drug; and parecoxib, a cyclo‐oxygenase‐2 inhibitor 9,11–15 . A single feasibility study investigated the role of acupuncture in this setting and concluded that the delivery of acupuncture was possible in this cohort of patients 8 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were no reported technical difficulties or complications of regional or neuroaxial techniques in these cohorts. Adjuvant pharmacological therapies investigated were: Dexmedetomidine, a potent alpha‐2 agonist with hypnotic, sedative, and analgesic properties; ketamine, a NMDA receptor antagonist with sedating, analgesic, and hypnotic actions; intravenous lidocaine, a sodium channel blocker with analgesic properties; ketorolac, a non‐steroidal anti‐inflammatory drug; and parecoxib, a cyclo‐oxygenase‐2 inhibitor 9,11–15 . A single feasibility study investigated the role of acupuncture in this setting and concluded that the delivery of acupuncture was possible in this cohort of patients 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Post‐operative pain scores were reported in eight studies (Table 2 and Supplementary Table S1). Four out of five studies included a control group and showed a significantly lower pain score at 24 h 9,11–13 . The multi‐modal approach by Hardman et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A non‐opioid analgesic is an essential tool for LDLT donors. Perioperative ketamine, lidocaine, gabapentin, and magnesium have been reported as useful adjuncts with opioid‐sparing effects in LDLT donors 46,50,51 . Non‐steroidal anti‐inflammatory drugs and acetaminophen have theoretical concerns for postoperative liver dysfunction and coagulation derangements but can be used judiciously.…”
Section: Essentials Of Donor Anesthetic Managementmentioning
confidence: 99%
“…1,3 Patients undergoing general abdominal surgery are already prone for prolonged bed rest and delayed mobilization therefore this PONV among such patients is not that much of a concern as compared to patients undergoing surgery for organ donation which are otherwise healthy and anticipate an uneventful and speedy recovery and discharge. 4,5,6 Therefore prophylaxis and prevention of PONV among such patients becomes much - ------------------------------------------------------------------------ Ondansetron is a 5-hydroxytryptamine 3 (5-HT3) receptor antagonists which have been widely used for the treatment of PONV. 7 However, its preemptive role in the prevention of PONV is under estimated where only few studies evaluated the incidence of PONV after prophylactic ondansetron administration before surgery.…”
Section: Introductionmentioning
confidence: 99%